The Effect of Special Speed Exercises on The Variables of The First Arc of 400-Meter Hurdles Race Under 20 Years of Age - Abdulhassan , Zahaa; Hameed , Intisar (Journal of Physical Education, 2024)
The research aims to prepare special speed exercises in the variables of the first arc of running the 400 m hurdles under 20 years of age and to identify the effect of special speed exercises in the variables of the first arc of running the 400 m hurdles under 20 years of age. To achieve the goal, the researchers used the experimental method by designing one group with two pre-and post-tests to suit the research problem. The research community included elite runners in the youth 400 m hurdles event for the year (2021-2023) and those with similar levels, numbering (8) athletes, who are of a community of origin. The sample was chosen intentionally and consisted of (6) players, representing 75% of the original population. After the tests and variables to be studied were determined, the researchers conducted the exploratory experiment as well as the pre-test, and then the exercises were applied during the training units. After completing the training units, the researchers conducted the post-test on the sample, and the researchers used the statistical package (Spss) (arithmetic mean, Standard deviation, paired samples t-test. The researchers concluded that special speed exercises contributed to increasing the rate of explosive power, as well as having a positive effect on the variables related to the first arc investigated, and that relying on the use of more specialized. exercises by mechanical principles and laws contributes to improving the level of the runner in terms of abilities and indicators related to effectiveness. As well as that training the athlete according to the centrifugal principle had a positive impact in standardizing the training intensity for 400m/hurdles event runners, The researchers recommend the need for trainers to rely on regulating training intensity according to mechanical indicators and laws that are specific to effectiveness, and the need to pay attention to the mechanical aspects that constitute a factor influencing the success of the event, in addition to paying attention to special speed training because it effectively affects the variables of the first arc and achieving 400-meter hurdles event